Enhanced adsorption of metal ions onto polyethyleneimine-impregnated palm shell activated carbon: Equilibrium studies - Yin, C.Y.; Aroua, M.K.; Daud, W.M.A.W. (Water Air and Soil Pollution, 2008)
In this study, palm shell activated carbon was impregnated with polyethyleneimine (PEI) and the effect of impregnation on batch adsorption of Ni2+, Cd2+or Pb2+ as well as the equilibrium behavior of adsorption of metal ions on PEI-impregnated AC were investigated. PEI impregnation evidently increased the single metal adsorption capacities of Ni2+ or Cd2+except for Pb2+, where its adsorption capacities were reduced by 16.67 and 19.55 for initial solution pH of 3 and 5 respectively. This suggested that PEI-impregnated AC could be used for selective separation of Pb2+ ions from other metal ions. The adsorption data of all the metal ions on both virgin and PEI-impregnated AC for both initial solution pH of 3 and 5 generally fitted the Langmuir and Redlich-Peterson isotherms considerably better than the Freundlich isotherm.